Prompt Return to Work after Bilateral Transforaminal Full-endoscopic Lateral Recess Decompression under Local Anesthesia: A Case Report - Sugiura, Kosuke; Yamashita, Kazuta; Manabe, Hiroaki; Ishihama, Yoshihiro; Tezuka, Fumitake; Takata, Yoichiro; Sakai, Toshinori; Maeda, Toru; Sairyo, Koichi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Transforaminal full-endoscopic lumbar diskectomy became established early in the 21st century. It can be performed under local anesthesia and requires only an 8-mm skin incision, making it the least invasive disk surgery method available. The full-endoscopic technique has recently been used to treat lumbar spinal canal stenosis. Here, we describe the outcome of simultaneous bilateral decompression of lumbar lateral recess stenosis via a transforaminal approach under local anesthesia in a 60-year-old man. The patient presented with a complaint of bilateral leg pain that was preventing him from standing and walking, and he had been able to continue his work as a dentist by treating patients while seated. Imaging studies revealed bilateral lumbar lateral recess stenosis with central herniated nucleus pulposus at L4/5. We performed simultaneous bilateral transforaminal full-endoscopic lumbar lateral recess decompression (TE-LRD) under local anesthesia. Both decompression and diskectomy were successfully completed without complications. Five days after TE-LRD, he was able to return to work, and 3 months after the surgery, he resumed playing golf. Full-endoscopic surgery under local anesthesia can be very effective in patients who need to return to work as soon as possible after surgery.
Keywords: transforaminal full-endoscopic lumbar lateral recess decompression; return to work; local anesthesia